2018
DOI: 10.1136/gutjnl-2018-316276
|View full text |Cite|
|
Sign up to set email alerts
|

Asia-Pacific working group consensus on non-variceal upper gastrointestinal bleeding: an update 2018

Abstract: Non-variceal upper gastrointestinal bleeding remains an important emergency condition, leading to significant morbidity and mortality. As endoscopic therapy is the ’gold standard' of management, treatment of these patients can be considered in three stages: pre-endoscopic treatment, endoscopic haemostasis and post-endoscopic management. Since publication of the Asia-Pacific consensus on non-variceal upper gastrointestinal bleeding (NVUGIB) 7 years ago, there have been significant advancements in the clinical m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
237
0
15

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 214 publications
(256 citation statements)
references
References 116 publications
4
237
0
15
Order By: Relevance
“…Some RCTs and meta‐analyses have shown that SLE prevented rebleeding in patients having peptic ulcers with a very high risk of active bleeding, while other studies had controversial results . To our knowledge, our study is the first to investigate the effect of SLE on post‐EVL bleeding in patients with cirrhosis and large EV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some RCTs and meta‐analyses have shown that SLE prevented rebleeding in patients having peptic ulcers with a very high risk of active bleeding, while other studies had controversial results . To our knowledge, our study is the first to investigate the effect of SLE on post‐EVL bleeding in patients with cirrhosis and large EV.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of post‐EVL bleeding has been reported to range from 7.8% within 6 weeks to 26% within one year from the index EVL . Several studies have focused on the effects of second‐look endoscopy (SLE) after therapeutic endoscopy for non‐variceal gastrointestinal bleeding (GIB) . However, to our knowledge, there have been no studies evaluating the efficacy of SLE in preventing early post‐EVL rebleeding so far.…”
Section: Introductionmentioning
confidence: 99%
“…The general strategy of intravenous PPI treatment for peptic ulcer bleeding is giving a high dose followed by continuous infusions . Since the effect of ilaprazole 20 mg was comparable to that of 30 mg, the lower was selected as the loading dose.…”
Section: Discussionmentioning
confidence: 99%
“…The general strategy of intravenous PPI treatment for peptic ulcer bleeding is giving a high dose followed by continuous infusions. [13][14][15] Since the effect of ilaprazole 20 mg was comparable to that of 30 mg, the lower was selected as the loading dose. The following infusion of 10 mg once daily for 2 days was selected because: (i) a previous study indicated that ilaprazole 10 once daily for 5 days provided stable PK and PD, and was well tolerated in healthy subjects 17 ; (ii) after receiving a bolus of 20 mg, ilaprazole 10 mg once daily for 2 days was assumed to produce comparable effect to that of 20 mg for 2 days based on a simulation using a mechanism-based PK/PD model (not published).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation